2018
DOI: 10.1002/jcp.26558
|View full text |Cite
|
Sign up to set email alerts
|

1800 MHz mobile phone irradiation induced oxidative and nitrosative stress leads to p53 dependent Bax mediated testicular apoptosis in mice,Mus musculus

Abstract: Present study was carried out to investigate the effect of long-term mobile phone radiation exposure in different operative modes (Dialing, Receiving, and Stand-by) on immature male mice. Three-week old male mice were exposed to mobile phone (1800 MHz) radiation for 3 hr/day for 120 days in different operative modes. To check the changes/alteration in testicular histoarchitecture and serum testosterone level, HE staining and ELISA was performed respectively. Further, we have checked the redox status (ROS, NO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…A decrease in the amount and survival rate of sperm cells was found in the RF group after exposing rats to 220 MHz pulsed modulated RF field for one month, which indicated that under this environment, 220 MHz pulsed modulated RF exposure might result in the disruption or impairment of spermatogenesis, which might affect the fertilization capacity of sperm. These findings are consistent with Shahin’s reports [10], who reported that 1800 MHz RF exposure produced by the base station of mobile phones (1.15 W/m 2 , SAR = 0.05 W/kg, 3 h/day for 120 days) decreased sperm count and sperm viability in mice. Meanwhile, Aitken [18] found that after exposure to 900 MHz RF produced by mobile phones (SAR = 0.09 W/kg, 12 h/day for seven days), the sperm count, survival rate of sperm and morphology did not change significantly.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…A decrease in the amount and survival rate of sperm cells was found in the RF group after exposing rats to 220 MHz pulsed modulated RF field for one month, which indicated that under this environment, 220 MHz pulsed modulated RF exposure might result in the disruption or impairment of spermatogenesis, which might affect the fertilization capacity of sperm. These findings are consistent with Shahin’s reports [10], who reported that 1800 MHz RF exposure produced by the base station of mobile phones (1.15 W/m 2 , SAR = 0.05 W/kg, 3 h/day for 120 days) decreased sperm count and sperm viability in mice. Meanwhile, Aitken [18] found that after exposure to 900 MHz RF produced by mobile phones (SAR = 0.09 W/kg, 12 h/day for seven days), the sperm count, survival rate of sperm and morphology did not change significantly.…”
Section: Discussionsupporting
confidence: 93%
“…Testosterone (T), a steroid hormone, produced mainly by LCs [26], is of vital importance to the development and function of male reproduction, and to the maintenance of normal spermatogenesis [27]. Shahin [10] reported that 1800 MHz RF exposure (1.15 W/m 2 , 3 h/day for 120 days) acted in the male reproductive tract of mice, in part by inhibiting T secretion from LCs. Lin [3] reported that exposing mouse LCs to a 1950 MHz continuous RF wave for 24 h (SAR = 3 W/kg) causes the level of T in the supernatant to diminish dramatically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Testicular protein samples (50 µg) from each group were resolved on 15% SDS‐PAGE at constant setting of 50 V for 30 min and then at 100 V for 1 hr, using the Mini‐PROTEAN tetra system, BIO‐RAD, The United States as mentioned elsewhere . Proteins were transferred from the polyacrylamide gels to PVDF membranes (Millipore, The United States) by electro‐blotting for 15 min in a Semi‐Dry blotting apparatus (TRANS‐BLOT SD, Semi‐dry transfer cell, BIO‐RAD, The United States) at constant setting of 15 V. Membrane was then blocked by 5% fat free skimmed (dry) milk in Tris buffered saline with 0.1% Tween‐20 (TBST) for 2 hr at room temperature.…”
Section: Methodsmentioning
confidence: 99%